Persepsi guru-guru di daerah Serian, Sarawak terhadap proses pencerapan oleh Guru Besar di bilik darjah - Akim, Jabri (2010)
The purpose of this study is to identify the teachers perception on the process of monitoring on teachers by principlals in the classroom. About 100 teachers comprises by male and female have been chosen as respondents randomly. The study also involves 8 primary school in the B category in Serian District, Samarahan, Sarawak. Survey method is using questionnaire as instrument. The data collected is analyzed using SPSS 16 version. Descriptive statistics is applied which involved the use of a one way ANOVA p>0.05. The finding of the study shows most teachers are pleased and agree with the monitoring process done by the principals. Inferential finding also shows that there is no significant in the process of monitoring among teachers of different sexs, ethnics and the teaching experiences. Teachers also agree that monitoring is important to upgrage professionalism. The findings of this study also shows that teachers should undergo the concept and principles behind monitoring to upgrade ones knowledge and to build a good two way relationship between both parties